Taksir Istikhdam Wasilah Flash Card Ala Istiab Al-Mufradat Lada Thalabah Fi Al-Fashl As-Sabi Fi Al-Madrasah Al-Tsanawiyah Al-Hukumiyah 2 Padang - Lusi Angraini; Rahmat Satria Dinata (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
The main problem in this research is "What is the effect of using a flash card media on the vocabulary comprehension of students in the class VII MTsN 2 Padang?". Then this research aims to know the vocabulary comprehension ability of students in the class VII MTsN 2 Padang before using flash card media, and to know the effectiveness of using flash card media on vocabulary comprehension of students in the class VII MTsN 2 Padang. The researcher used the quantitative approach by the experimental research method, and the method of data collection is the test and its tools, and the data collection method used the questions in oral and written form, and in analyzing the data with a T-test using the SPSS 20. The researcher found that the data was normally distributed and homogeneous with a significance value of > 0.05 as a requirement for the T test. The results of the research indicated that the vocabulary comprehension ability of students before using flash card means that among 30 students, 26 students were unsuccessful in the minimum scale of 80 KKM, with an average value of 62.2. Then the "T" test indicates that the result of the calculation is -38,379 that is greater than the result of the table -73,971. The result of sig (2-tailed) is 0.05 is greater than 0.000. So, the researcher concludes that Ho is rejected and Ha is accepted. So, The use of flas card is effective on vocabulary comprehension of students in the class VII MTsN 2 Padang.  Keywords: Media; Flash Card; Arabic; Vocabulary